Patient-Specific Pre-Treatment VMAT Plan Verification Using Gamma Passing Rates - M. Z. Arsalan; M. B. Kakakhel; M. Shamshad; T. A. Afridi (National Research and Innovation Agency, 2023)
Continuous gantry motion, continuous beam modulation, and variable dose rate are used in volumetric modulated arc therapy (VMAT) to obtain highly conformal radiation therapy dose distributions. Several errors during daily radiation therapy treatment can be sources of uncertainties in dose delivery. These errors include monitor unit calculation errors and other human mistakes. Due to the uncertainties in the excessively modulated VMAT plan, the intended dose distribution is not delivered perfectly, leading to a mismatch between the measured and planned dose distributions. This necessitates an extensive and effective quality assurance (QA) program for both machine and patient. In this study, VMAT QA plan verification of 62 head and neck (HN) and 19 prostate cases was done using Octavius 4D setup with its associating VeriSoft gamma analysis software. The plans showed a maximum 3D gamma passing rate with 4 mm/3 % gamma acceptance criteria, i.e., 99.7 % for the HN cancer cases and 99.5 % for the prostate cancer cases. Local gamma analysis was also performed for both regions. Furthermore, 2D and volumetric gamma analyses were also carried out. Gamma analysis with respect to different axis was also carried out. It was known that the transversal axis showed the highest gamma passing rate in both HN and prostate cases, i.e., 99.17 % and 98.3 %, respectively. The transverse axis came to be a better fit for the planned dose distribution.